2002
DOI: 10.1210/endo.143.7.8879
|View full text |Cite
|
Sign up to set email alerts
|

Specific Detection of Type III Iodothyronine Deiodinase Protein in Chicken Cerebellar Purkinje Cells

Abstract: Because iodothyronine deiodinases play a crucial role in the regulation of the available intracellular T(3) concentration, it is important to determine their cellular localization. In brain, the presence of type III iodothyronine deiodinase (D3) seems to be important to maintain homeostasis of T(3) levels. Until now, no cellular localization pattern of the D3 protein was reported in chicken brain. In this study polyclonal antisera were produced against specific peptides corresponding to the D3 amino acid seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Furthermore, D2 mRNA was demonstrated in elongated cell clusters throughout the brain, comparable with the results recently described by Gereben et al (2004). Comparison of the D2 protein distribution with that of D1 and D3 protein within the choroid plexus using earlier developed antisera (Verhoelst et al 2002(Verhoelst et al , 2003, led to the conclusion that neither of the two other deiodinase proteins are present in the choroid plexus. The staining in the cuboidal cells therefore solely originates from the D2 protein.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Furthermore, D2 mRNA was demonstrated in elongated cell clusters throughout the brain, comparable with the results recently described by Gereben et al (2004). Comparison of the D2 protein distribution with that of D1 and D3 protein within the choroid plexus using earlier developed antisera (Verhoelst et al 2002(Verhoelst et al , 2003, led to the conclusion that neither of the two other deiodinase proteins are present in the choroid plexus. The staining in the cuboidal cells therefore solely originates from the D2 protein.…”
Section: Discussionsupporting
confidence: 85%
“…Triiodothyronine is then supplied to the neurons, which mainly express D3, for further deiodination and inactivation of the thyroid hormones (Guadaño-Ferraz et al 1997). In chicken, it has been shown that D3 protein is expressed in the Purkinje cells of the cerebellum, again a proof of a neuronal D3 expression (Verhoelst et al 2002). However, the present study reports the presence of D2 in a nonneuronal cell type, namely the epithelial cells of the choroid plexus.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…D2 is localized mainly in the glial cells (Guadano-Ferraz et al, 1997), but the Purkinje cell localization has been observed during specific developmental periods (Verhoelst et al, 2005). D3 is localized mainly in neurons including the Purkinje cells (Verhoelst et al, 2002). D3 activity increases in hyperthyroidism, and decreases in hypothyroidism (Dratman et al, 1983) and is thought to protect neurons from excessive T3 levels.…”
Section: Brain Th Homeostasis: Contribution Of Circulating Vs Locallmentioning
confidence: 99%